Analysis of The Influence of Korean Wave, Brand Ambassador, and Brand Image on Purchasing Decisions for Korean Skincare Products in The Beauty Industry - Dewi Nely Sahadah; Deny Solaiman; Fransisca Sestri Goestjahyanti; Winanti; Istajib Kulla Himmy’azz; Tatang Iman Sadewa (Journal of E-business and Management Science, 2024)
This study aims to examine the effect of the Korean Wave, Brand Ambassador, and Brand Image on Purchasing Decisions for Korean Skincare Products in the Beauty Industry on the background of the Korean Wave or Hallyu is a global phenomenon that describes the spread of Korean pop culture, including music, drama, and fashion which has increased consumer buying interest in Korean products. With the research variables Korean Wave (X1), Brand Ambassador (X2), and Brand Image (X3) Against Purchasing Decisions (Y) Korean skincare products in the Beauty Industry. The method used is quantitative, the population of this study was conducted in the user section of skincare products totaling 100 people who were sampled. The sampling technique uses the Lemeshow formula. Data collection using a Likert scale asks for the respondent's statement regarding the respondent's level of agreement with the questionnaire statement. The data obtained was analyzed using multiple linear regression techniques to identify the relationship and influence of the three dependent variables, namely purchasing decisions. The results of the study can be seen from the value of the multiple correlation level of 0.837, this shows that the correlation level has a very strong influence. The coefficient of determination of 0.837 means that the Korean Wave, Brand Ambassador, and Brand Image variables on purchasing decisions for Korean Skincare products in the Beauty Industry are 70.1%, and the remaining 29.9%% is influenced by other variables not examined in this study. Meanwhile, the results of the hypothesis test simultaneously show a significant effect because Fcount>Ftable 74,953>2,699 with a Sig value of 0.000<0.05, there is a significant influence between the Korean Wave (X1), Brand Ambassador (X2) and Brand Image (X3) variables on Purchasing Decisions (Y).